Training returns among informal workers: Evidence from urban sites in Kenya and Tanzania - Nina Torm (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2023)
Human capital development, including both education and post-school training, has been a central part of the development strategies of most countries, because it contributes to economic growth, both through raising productivity and facilitating the use of new technologies. In addition, training is often categorised as a type of transformative social protection allowing workers to raise earnings through widening their skills base. This study uses mixed methods to examine the returns to (formal and informal) training, for informal workers operating in the sectors of construction, micro-trade and transport in urban areas of Kenya and Tanzania. The quantitative analysis finds that workers, who have undertaken formal training, have earnings that are between 16-21% higher than workers with no training, and that receiving on-the-job training or being trained by a family member, does not provide as substantial a return as formal training does. Moreover, training gains differ by gender, location, sector and worker-type, pointing to the need to better tailor training initiatives to the needs of specific workers. In support, evidence from interviews also illuminates the role of informal worker associations in terms of offering and/or providing access to training, in addition, to other social protection measures. By focussing on informal workers, the study contributes to the existing literature, which mostly looks at training returns among formal workers. However, given that in lowand middle-income countries workers often make a living in the informal sector, it is imperative to understand how training may benefit and protect this segment of the workforce. In terms of policy relevance, the results show the importance of strengthening formal training institutions to further decent work, also in informal settings. In helping to bridge the skills divide, training plays an important part towards formalising labour markets by enabling more qualified informal workers to find productive formal employment.
Keywords: 330; Informelle Wirtschaft; Berufsbildung; Bildungsertrag; Kenia; Tansania